Cognitive Learning Theory from an Islamic Perspective: A Conceptual and Content Analysis - Lubis, Khairan Nur; Deliani, Nurfarida; Batubara, Juliana; Akbar, Ali (El-Rusyd, 2025)
Cognitive Learning Theory emphasizes mental processes as the foundation of how individuals acquire, organize, and process knowledge. Rather than viewing learning solely as a response to external stimuli, this theory highlights the role of cognitive structures, perception, memory, attention, and higher-order thinking. This study aims to examine the core concepts of Cognitive Learning Theory and analyze their relevance from an Islamic perspective. Using a qualitative content analysis approach, this study reviews key sources in educational psychology, peer-reviewed journals, and Islamic literature, including Quranic verses and the perspectives of Muslim scholars. The findings indicate that fundamental cognitive concepts such as reason, understanding, reflective thinking, and internal reinforcement are strongly aligned with Islamic educational principles. The Quran emphasizes the use of reason through concepts such as tadabbur, tafakkur, and ta‘aqqul, which correspond to cognitive processes highlighted in modern learning theory. This study argues that integrating Cognitive Learning Theory with Islamic educational values contributes to the development of learning strategies that are both cognitively effective and ethically grounded.